Comparative analysis of selected aspects of web application architectures - Krzysztoń, Łukasz; Łatwiński, Konrad; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2025)
The article presents a comparative analysis of two web application architectures: microservices and modular monoliths. The research focuses on evaluating the impact of infrastructure, inter-component communication, and horizontal scaling on system performance. For the purpose of the study, a dedicated system was implemented in two versions: as microservices and as a modular monolith. This allowed for a direct comparison of both architectures under identical experimental conditions. The application underwent a series of performance tests, including simulations of various load levels and analysis of response times in different operational scenarios. The collected data was presented in the form of statistics and graphs, facilitating result interpretation and allowing for the verification of the research hypotheses.